(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
This article develops the basics of the theory of English terms into Ukrainian. The peculiarities of non-equivalents terms translation into Ukrainian are determined; general definition of the notion «term» in linguistics is generalized, common features in notion definitions by different scientists are outlined and term main characteristics are indicated. The ways of translating English terms into Ukrainian are considered and the features of each method are outlined. Particular attention is paid to the translation of multicomponent terms and defined two main stages of their translation; the main incorrect translation causes are considered. Translating terms from English into Ukrainian, linguists are primarily trying to find a lexical equivalent – a constant lexical correspondence that exactly coincides with the meaning of the word. This task is rather complicated, since many terms have appeared relatively recently, therefore it is not always possible to impose them on the realities of our country. If it is impossible to find absolute equivalents then the absolute equivalent of the relative is allowed. Among the ways of translating terms the next ones are considered: the untranslatable adoption of terms method (it is not recommended for widespread use, since «excessive adoption» is often carried out, while in the language the equivalent of the term already exists), adaptive transcoding (it is recommended to use if it is necessary to create a clearly defined term), linguistic calque (in some cases this method is integral for translating specialized terms), explication or descriptive translation (when a simple term is replaced by a phrase that absolutely conveys its meaning), inversion (change the phrase components order) and substantiation (using Ukrainian word with a narrower subject-logical meaning than the English one has). While translating non-equivalents terms, a combination of several translation techniques can be combined simultaneously. Complex terms translation involves two stages: analytical and synthetic. When translating the terms, it is necessary to take into consideration the context of the whole text. The translation of terms is the core of scientific and technical translation, so it is important to know the features of the translation of this vocabulary layer to achieve maximum equivalence.